1995
DOI: 10.1139/m95-004
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence and transcriptional analysis of the celD β-glucanase gene from Ruminococcus flavefaciens FD-1

Abstract: The nucleotide sequence of the celD gene, which encodes endoglucanase and xylanase activity, from Ruminococcus flavefaciens FD-1 was determined. The DNA sequence of celD contains an open reading frame of 1215 nucleotides that encodes a polypeptide of 405 amino acids with a molecular mass of 44,631 Da. The primary amino acid sequence of CelD was screened against the GenBank data base for similar polypeptide sequences and the analysis indicated that CelD has common features with endoglucanases from the family E … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…This processive endoglucanase was up-regulated 4.49 fold. CelA (ORF00507) and CelD (ORF01899) were unaffected (1.10 fold) and up-regulated (4.93 fold) respectively (Table S10), which is consistent with previous results [18], [58]. CelB (ORF01869) was unaffected (1.13 fold; Table S9), which contradicts previous data that indicated that it was inducible by cellulose [17], [58], [59].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This processive endoglucanase was up-regulated 4.49 fold. CelA (ORF00507) and CelD (ORF01899) were unaffected (1.10 fold) and up-regulated (4.93 fold) respectively (Table S10), which is consistent with previous results [18], [58]. CelB (ORF01869) was unaffected (1.13 fold; Table S9), which contradicts previous data that indicated that it was inducible by cellulose [17], [58], [59].…”
Section: Resultssupporting
confidence: 89%
“…Difficulties were encountered in initial fractionation of these enzymes as they appeared to exist in high-molecular-weight protein complexes resembling cellulosomes [12], [13], and enzymatic activity was lost rapidly when the complexes were disrupted [12]. Individual β-glucanase genes ( celA , celB , celC , and celD ) were cloned from R. flavefaciens FD-1 with a view to studying their regulation [14], [15], [16], [17], [18]. Meanwhile, parallel studies in the related R. flavefaciens strain 17 also led to the sequence analysis of a number of xylanases and cellulases.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are many reports of single-domain endoglucanases from R. flavefaciens and R. albus that are smaller than 50 kDa (30,33,40,41,42). This may suggest that not all cellulases are cellulosome associated in ruminococci.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of cloned polysaccharidase genes has, however, produced somewhat conflicting evidence concerning the molecular organization of these enzymes, and the mechanisms by which they might attach to their substrate and to the cell surface have thus remained unclear. Many of the cellulase genes first isolated from R. flavefaciens and R. albus (7,18,30,33,40,41) were reported to encode single domain enzymes smaller than 50 kDa that carry no obvious substrate binding domains, and no regions that might be responsible for the types of protein-protein interactions that are found, for example, in the assembly of cellulosome complexes from Clostridium spp. (3, 4, 9).…”
mentioning
confidence: 99%
“…EndB is a protein of 808 amino acids with a domain structure consisting of a signal peptide, a GH44 catalytic domain, an unknown CBM type, and a type I dockerin domain ( Figure 1) (Rincón et al 2001). CelB is a sequence of 827 amino acids for a multidomain β-glucanase protein, although this putative protein is also reported as having only 632 amino acids (Vercoe et al 1995, Warner 2007.…”
Section: Paenibacillus Speciesmentioning
confidence: 99%